Autosomal genetic control of human gene expression does not differ across the sexes. Issue 1 (December 2016) - Kassam, Irfahan; Lloyd-Jones, Luke; Holloway, Alexander; Small, Kerrin; Zeng, Biao; Bakshi, Andrew; Metspalu, Andres; Gibson, Greg; Spector, Tim; Esko, Tonu; Montgomery, Grant; Powell, Joseph; et al.
Abstract Background Despite their nearly identical genomes, males and females differ in risk, incidence, prevalence, severity and age-at-onset of many diseases. Sexual dimorphism is also seen in human autosomal gene expression, and has largely been explored by examining the contribution of genotype-by-sex interactions to variation in gene expression. Results In this study, we use data from a mixture of pedigree and unrelated individuals with verified European ancestry to investigate the sex-specific genetic architecture of gene expression measured in whole blood acrossn =1048 males andn =1005 females by treating gene expression intensities in the sexes as two distinct traits and estimating the genetic correlation (r G ) between them. These correlations measure the similarity of the combined additive genetic effects of all single-nucleotide polymorphisms across the autosomal chromosomes, and thus the level of common genetic control of gene expression across the sexes. Genetic correlations are estimated across the sexes for the expression levels of 12, 528 autosomal gene expression probes using bivariate GREML, and tested for differences in autosomal genetic control of gene expression across the sexes. Overall, no deviation of the distribution of test statistics is observed from that expected under the null hypothesis of a common autosomal genetic architecture for gene expression across the sexes. Conclusions These results suggest that males and females share the same common genetic control of gene expression.